1988
DOI: 10.1111/j.1365-2125.1988.tb05315.x
|View full text |Cite
|
Sign up to set email alerts
|

Haem arginate improves hepatic oxidative metabolism in variegate porphyria.

Abstract: 1. The elimination of antipyrine was investigated before and after intravenous administration of haem arginate (3 mg haem kg‐1 day‐1 on three or four successive days) to six patients with variegate porphyria in remission. 2. Haem arginate decreased the faecal content of protoporphyrin from 557 +/‐ 91 to 118 +/‐ 32 (mean +/‐ s.e. mean) and of coproporphyrin from 144 +/‐ 19 to 19 +/‐ 3 nmol g‐1 dry weight. 3. Before haem treatment antipyrine elimination half‐life was long (30.5 +/‐ 5.6 h), but the treatment decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Tin protoporphyrin, other metalloporphyrins and heme reduce ALA synthase activity (6, 20, 22, 23, 36, 371, and these compounds have been used to reduce overproduction of heme precursors in patients with acute porphyria (12)(13)(14)(15)36,38). Tin-chelated porphyrins can cause cutaneous photosensitivity (36, 40-42,44,45) and are not readily catabolized in viva (36, 46, 651, raising concerns about possible long-term adverse effects of these compounds (41-45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tin protoporphyrin, other metalloporphyrins and heme reduce ALA synthase activity (6, 20, 22, 23, 36, 371, and these compounds have been used to reduce overproduction of heme precursors in patients with acute porphyria (12)(13)(14)(15)36,38). Tin-chelated porphyrins can cause cutaneous photosensitivity (36, 40-42,44,45) and are not readily catabolized in viva (36, 46, 651, raising concerns about possible long-term adverse effects of these compounds (41-45).…”
Section: Discussionmentioning
confidence: 99%
“…Activity of this enzyme is elevated in human subjects with acute porphyria , in whom occurrence of clinical illness is associated with increased excretion of porphyrins and porphyrin precursors, the biochemical hallmarks of the acute porphyrias. The treatment of choice for all but the mildest attacks of acute porphyria is intravenous heme (11)(12)(13)(14)(15), first described 22 yr ago (15). Heme reduces hepatic ALA synthase levels in various experimental models of acute porphyria (16)(17)(18)(19) and undoubtedly has the same effect in patients with acute porphyria (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In human studies on acute porphyrias, exogenous heme corrects impairments in hepatic oxidative drug metabolism and normalizes porphyrin overproduction in variegate porphyria. 126 It is effective in repleting deficient heme pools and heme proteins, 118 in increasing Cyp450 activity in AIP 127 and has an isoenzyme-specific influence on Cyp450 drug metabolism. 128 Heme is the prosthetic group in many important liver enzymes and is involved in regulating the amount and activity of cytochrome P450.…”
Section: Prelude To Liver Transplantationmentioning
confidence: 99%
“…In 1987 Herrick et al in Scotland [ 79 ] treated seven attacks in five patients: decrease of 5-ALA and PBG and improvement of clearance of antipyrin (which is degraded in the liver by CYP enzymes) were observed. In 1988 Tokola et al, (Finland) reported on six patients with VP with respect to antipyrin clearance [ 80 ]. In 1988 Volin et al [ 81 ] did not find adverse effects on hemostasis in healthy volunteers treated with heme arginate.…”
Section: Therapymentioning
confidence: 99%